Enterprise to cloud security assessment a method using OSSTMM 3.0 concepts - Ronivon, C.; Serrão, C. (Proceedings of the International Conference on Knowledge Discovery and Information Retrieval and the International Conference on Knowledge Management and Information Sharing, 2013)
Much has been talked about security, and with the wide spread and adoption of Cloud computing, the talk has followed the buzz and put Cloud Security in the spotlights. Security guides for the Cloud has been published, but we understand that is still missing a practical assessment methodology that would allow organizations to quick understand how the security of their assets are impacted when it is farmed out to Public Clouds. Our contribution to address this problem is a method to isolate the organization’s assets from the environment it is hosted, and compare metrics from the environment only. This method provides the important benefit of allowing the organization to determine how security will be impacted without having to actually migrate its resources.